Application of Class Supervision to Improve Professional Competency of Teachers at SMP Negeri 1 Padangsidimpuan - Torang Siregar (Jurnal Intelek Insan Cendikia, 2024)
Abstract The role of the school principal as a leader in the education process and improving the quality of human resources related to teacher professionalism is needed. One of the roles of the school principal is as a supervisor in the learning process. Through the supervisor's duties, it is hoped that the school principal will be able to provide evaluations in the implementation of the Main Duties and Functions of teachers so as to create teacher professionalism. In this study, we tried to improve the results of teacher supervision carried out over 2 cycles, with results increasing in each cycle. In cycle 1, the RPP assessment showed that there were 8 respondents who got very good marks and 3 respondents who got good scores. for the assessment of supervision of visits in the classroom, it showed that there were 8 respondents who got very good marks and 3 who got good scores. The average results of the instruments for assessing Learning Plans and Observations in the classroom showed 8 respondents who got very good scores and 3 who got good scores. in cycle 2 for the RPP assessment, it showed that there were 9 respondents who got very good marks and 2 respondents who got good scores. For the assessment of supervision of visits in the classroom, it was shown that there were 10 respondents who got very good marks and 1 who got good marks. The average results of the instruments for assessing Learning Plans and Observations in the classroom showed 9 respondents who got very good scores and 2 who got good scores. Another result obtained in this classroom action research was that although the assessment predicate remained very good, there was an increase in the scores obtained from cycle 1 to cycle 2. in cycle 1 the score for very good was still in the range of eight tens, but in cycle 2 the score for very good was in the range of 90. With these results, this research was considered successful in accordance with the established success criteria.